OPTIMASI PENJADWALAN WAKTU KERJA MENGGUNAKAN INTEGER PROGRAMMING - Windra Tahir; Djihad Wungguli; Muhamad Rezky Friesta Payu (Universitas Negeri Gorontalo, 2019)
Scheduling workers is one of the problems faced by every company. The regulations set by the company, the availability of the number of workers, and the division of labor are the determining factors in the scheduling system. This worker scheduling problem can be modeled as an Integer Programming problem. Integer Programming is an optimization technique with linear objective functions, linear constraint functions, and integer variables. This paper discusses the formulation of worker scheduling problems in the form of Integer Programming with workers in companies engaged in the production of Crumb Rubber with the objective function of minimizing the number of workers employed. The next model is implemented using the help of LINGO 11.0 software. The implementation results show that the model is able to produce optimal employee schedules.